Miocarditis fulminante, simuladora de sindrome coronario agudo (2014)
ABSTRACT: We report the case of a 48 year-old man with chest pain and history of coronary and autoimmune diseases, who developed acute heart failure and hemodynamic collapse. We present his clinical evolution and the tests that allowed the diagnosis of fulminant myocarditis secondary to systemic lupus erythematosus. A review of the most important aspects of this disease is also included.